(3QSGdI JhHjN GHf CHj MUjgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe GdCdg GdeeVi dCeQg hEQGOJg ZPG CMH HeTjJg hcdeJg CWGd Gddg HbGA GdTjhN GdMaXI GdGWgGQ s
(3BNQgG (B:s
(3hGf GHGg GdNhfg GdeQJOhf hgh MSH GdYHO GdVYja hGdMeO ddg hMOg hGdTcQ dhdjg GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis